Energy-environmental performance of Thai's cement industry - Natanee Vorayos (2020)
© 2019 One of the most important mechanisms to improve the sustainability of each country are monitoring the performance of the industries not only in the energy perspective but also the environmental point of view and setting the improvement goal. This study presents an indicator that can reflect both of energy consumption and greenhouse gas emission simultaneously called energy-environmental performance index. The cement industry is selected as the case study due to its important role in Thai's economic system and because it has high energy and greenhouse gas intensities. The performance of the sector during 2010–2016 are evaluated from the statistical data of volume produced, gross outputs in monetary value, energy consumption, raw material-to-clinker ratio, clinker-to-cement ratio and composition of clinker. The result shows that the energy-environmental performance index under the current situation of cement sector is 0.70. This is the average performance for the sector-level and can be used as the benchmarking for the company in the same industry. Since all data required for the calculation are the basic data for most companies, it means that the company can estimate its performance at the company level as well. Besides, this study also uses the statistical data and results in 2010–2016 to forecast the baseline performance in 2025 and then uses the baseline performance including target from the energy conservation plan and greenhouse gas mitigation plan to estimate the performance target. It could be found that the energy-environmental performance target of cement industry in 2025 is 0.75.